Tanzania : 2002 Article IV Consultation, Fifth Review Under the Poverty Reduction and Growth Facility and Request for an Extension of the Arrangement and Waiver of Performance Criterion-Staff Report; Public Information Notice and News Brief on the Executive Board Discussion; and Statement by the Executive Director for Tanzania. (IMF Staff Country Reports; Country Report, 2003)
This paper examines Tanzania's 2002 Article IV Consultation, Fifth Review Under the Poverty Reduction and Growth Facility (PRGF) and a Request for an Extension of the Arrangement and Waiver of Performance Criterion. Tanzania's performance under the PRGF-supported program has been broadly on track. All the qualitative performance criteria through end-June 2002 were observed, but quantitative benchmarks on reserve money, extrabudgetary expenditure, and the accumulation of domestic budgetary arrears were not met. One structural performance criterion, relating to the amendment of legislation to tighten approval procedures for incurring or guaranteeing new foreign borrowing, was not observed.